An investigation of distress tolerance and difficulties in emotion regulation in the drive for muscularity among women. (June 2020) - Cunningham, Mitchell L.; Szabo, Marianna; Rodgers, Rachel F.; Franko, Debra L.; Eddy, Kamryn T.; Thomas, Jennifer J.; Murray, Stuart B.; Griffiths, Scott
Highlights: Female drive for muscularity is likely associated with aversive emotions. We examined emotion regulation and distress tolerance in relation to this drive. Emotional non-acceptance was associated with muscularity concerns and behaviors. The urge to reduce distress was associated with muscularity concerns and behaviors. These emotional domains may be targeted to assist women with muscularity concerns. Abstract: Despite the negative emotional experiences that often accompany the pursuit of an idealized appearance, we know little about emotion regulation in the context of female drive for muscularity. To address this knowledge gap, we examined whether distress tolerance and difficulties in emotion regulation were significantly associated with the drive for toned muscularity among women. In this study, 221 Australian university women completed an online survey assessing drive for muscularity, distress tolerance, and emotion regulation difficulties. Results revealed that low distress tolerance and emotion regulation difficulties were positively associated with drive for muscularity attitudes and behaviors, after controlling for body mass index and general negative affect. Our findings suggest that women with a range of distress tolerance and emotion regulation difficulties, particularly the urgent need to regulate, and non-acceptance of, distress may experience a higher drive for muscularity. This study provides preliminary evidence that specific aspects of distress tolerance and poor emotion regulation may be promising targets in prevention and treatment interventions aimed to address the excessive drive for muscularity among women.